Turismo em lagoas costeiras e valoração ambiental em Osório, Rio Grande do Sul - Carvalho, Rita Gabriela Araujo (My University, 2017)
Destinations located in coastal regions, such as lake environments, are considered the most popular in the world today. Brazil stands out for its extensive coast and for having attractions for those who enjoy the sun and the beaches. In Rio Grande do Sul, a southernmost state in Brazil, there is a coastal region found to be unique in the world. It consists of a privileged region that has a coastal plain with 37,000 km² as well as approximately 100 freshwater lakes along its coast. The area of study covers the city of Osório, located on the north coast of the state, formed by a lake complex. In addition, these lakes are embedded in a mosaic of terrestrial ecosystems with a high diversity that harbor endangered species. Thus, taking into account the importance of these environments and the anthropic pressures that threaten them, the present study intended to characterize the industry of tourism in the lakes of Osório by checking the residents’ Willingness to Pay (WTP) for their preservation using the Contingent Valuation Method (CVM). Results show that besides its ecological value, this web of lakes has a historical-cultural heritage not yet explored by tourism. Among the people interviewed, over 70% are willing to pay for the preservation of the coastal lakes. By means of the residents’ WTP, a total annual value of R$ 931,491.86 was estimated so that the lakes can be preserved. This research may contribute to help one think of lakes as plural environments, providing the community and the public administration of Osório with the parameters to create a future financial fund aimed at preserving these ecosystems.
Os destinos localizados na região costeira, incluso os ambientes lacustres, são considerados os mais populares na atualidade no mundo. O Brasil destaca-se por sua extensa costa e por possuir atrativos relacionados ao sol e praia. No extremo sul do Brasil, no estado do Rio Grande do Sul, encontra-se uma região costeira considerada única no mundo. Essa região é privilegiada, pois além de possuir uma planície costeira com 37.000 km², ao longo de sua costa há aproximadamente 100 lagoas de água doce. A área de estudo abrange o município de Osório, localizado no Litoral Norte do estado, formado por um complexo lacustre com cerca de 23 lagoas. Além disso, essas lagoas estão inseridas em um mosaico de ecossistemas terrestres com uma alta diversidade, abrigando espécies ameaçadas de extinção. Assim, levando em conta a importância desses ambientes e as pressões antrópicas que o ameaçam, o presente estudo objetivou caracterizar o turismo nas lagoas de Osório, verificando a Disposição a Pagar-DAP dos moradores para sua preservação, utilizando-se do Método de Valoração Contingente. Os resultados do estudo demonstraram que essa teia de lagoas, além de seu valor ecológico, dispõe de um patrimônio histórico-cultural, ainda não explorados pelo turismo. Entre os entrevistados, mais de 70% estão dispostos a pagar pela preservação das lagoas costeiras. Estimou-se, por meio da DAP dos moradores, um valor total anual de R$ 931.491,86 para a preservação das lagoas costeiras. Acredita-se que esta pesquisa poderá contribuir para pensar as lagoas como ambientes plurais, fornecendo a comunidade e a gestão pública de Osório parâmetros para criação de um futuro fundo financeiro que vise a preservação desses ecossistemas.
Keywords: Turismo - Osório (RS); Turismo - Aspectos ambientais; Costa - Rio Grande do Sul; Tourist trade - Osório (Brazil); Tourist trade - Environmental aspects; Coasts - Rio Grande do Sul (Brazil)